PRECEDENT PHENOMENA IN THE MEDIA: A TOOL FOR SHAPING PUBLIC OPINION IN THE REPUBLIC OF UZBEKISTAN AND THE RUSSIAN FEDERATION - Tursunoy Muhiddinovna Parmonova; Sandugash Erkinbekovna Kaldigozova (Web of Journals Publishing, 2025)
This article examines the role of precedent phenomena in shaping public opinion through the media in Russia and Uzbekistan.
Keywords: Precedent, phenomena, public opinion, mass media, identity, manipulation, patriotism, communication.